Minimizing Learning Loss Among Students During the Covid-19: The Case of Bahrain - Al-Hattami, Abdulghani Ali; Alghazo, Yazan Mohammad (Journal of Educational and Psychological Sciences, 2022)
The article addresses the issue of learning loss among students during the Covid-19 era of schooling, where most countries around the world opted for online schooling options but had no prior preparation for a large-scale switch towards an utterly online learning system. Background information about learning loss and several contributing factors to learning loss are discussed. Finally, the authors present the case of the Kingdom of Bahrain. They argue that it had been one of the successful models of adapting to meet student needs during the abrupt and sudden change to the learning environment and the switch to online learning. Further solutions to deal with the education loss are suggested at the end of the paper.
Keywords: Learning loss; online teaching; Covid-19; Bahrain